2023
DOI: 10.1002/pld3.540
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting genomic regions and underlying sheath blight resistance traits in rice (Oryza sativa L.) using a genome‐wide association study

R Naveenkumar,
Annamalai Anandan,
Seenichamy Rathinam Prabhukarthikeyan
et al.

Abstract: The productivity of rice is greatly affected by the infection of the plant pathogenic fungus Rhizoctonia solani, which causes a significant grain yield reduction globally. There exist a limited number of rice accessions that are available to develop sheath blight resistance (ShB). Our objective was to identify a good source of the ShB resistance, understand the heritability, and trait interactions, and identify the genomic regions for ShB resistance traits by genome‐wide association studies (GWAS). In the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
(141 reference statements)
0
0
0
Order By: Relevance
“…Increasing studies have shown that resistance to rice ShB is a typical quantitative trait controlled by multiple genes without major resistance genes [6][7][8][9][10]. So far, at least 50 ShB resistance quantitative loci (QTLs) have been identified with the traditional gene-mapping method, and several candidate loci or genes have been uncovered by genome-wide association analysis [11][12][13][14][15][16][17][18][19][20]. However, due to the fact that very few of these QTLs have been isolated and most of them carry only small resistance effects and their locations have not been fine-mapped, these QTLs have been seldom used in breeding practices for ShB resistance [21].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing studies have shown that resistance to rice ShB is a typical quantitative trait controlled by multiple genes without major resistance genes [6][7][8][9][10]. So far, at least 50 ShB resistance quantitative loci (QTLs) have been identified with the traditional gene-mapping method, and several candidate loci or genes have been uncovered by genome-wide association analysis [11][12][13][14][15][16][17][18][19][20]. However, due to the fact that very few of these QTLs have been isolated and most of them carry only small resistance effects and their locations have not been fine-mapped, these QTLs have been seldom used in breeding practices for ShB resistance [21].…”
Section: Introductionmentioning
confidence: 99%